Mathematical methods of signal analysis applied in medical diagnostic - Ciecierski, Konrad A. (Zielona Góra: Uniwersytet Zielonogórski)
Digital signal processing, such as filtering, information extraction, and fusion of various results, is currently an integral part of advanced medical therapies. It is especially important in neurosurgery during deep-brain stimulation procedures. In such procedures, the surgical target is accessed using special electrodes while not being directly visible. This requires very precise identification of brain structures in 3D space throughout the surgery.
Keywords: classification; decision support systems; signal filtering; data fusion; temporal analysis